2012
DOI: 10.1073/pnas.1107721109
|View full text |Cite
|
Sign up to set email alerts
|

Functional characteristics of developmental dyslexia in left-hemispheric posterior brain regions predate reading onset

Abstract: Individuals with developmental dyslexia (DD) show a disruption in posterior left-hemispheric neural networks during phonological processing. Additionally, compensatory mechanisms in children and adults with DD have been located within frontal brain areas. However, it remains unclear when and how differences in posterior left-hemispheric networks manifest and whether compensatory mechanisms have already started to develop in the prereading brain. Here we investigate functional networks during phonological proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
190
3
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(221 citation statements)
references
References 72 publications
(128 reference statements)
18
190
3
5
Order By: Relevance
“…Previous neuroimaging studies on reading and phonological tasks have reported, in dyslexic participants relative to controls, higher activity in IFG (47,48) and less activation mostly in the left parietotemporal, left occipitotemporal, and left frontal areas (49)(50)(51), although this is not the case in all studies (e.g., refs. 52, 53).…”
Section: Discussioncontrasting
confidence: 39%
“…Previous neuroimaging studies on reading and phonological tasks have reported, in dyslexic participants relative to controls, higher activity in IFG (47,48) and less activation mostly in the left parietotemporal, left occipitotemporal, and left frontal areas (49)(50)(51), although this is not the case in all studies (e.g., refs. 52, 53).…”
Section: Discussioncontrasting
confidence: 39%
“…An fMRI study in at-risk kindergartners reported hypoactivations at left posterior regions before formal reading instruction at brain areas corresponding to previously identified areas in adult and school-aged dyslexics (Raschle, Zuk & Gaab, 2012). Brain activity at left occipito-temporal and temporo-parietal areas was positively correlated with pre-reading skills in both groups.…”
Section: Interaction Of Internal Resources and External Factors In Scmentioning
confidence: 72%
“…It has been also seen that several dissimilar genetic profiles can lead to similarly manifesting phenotypes of dyslexia (Pennington, 2006;Willcutt et al, 2010). Many brain studies show anatomic and functional abnormalities in the brains of at-risk children before formal reading instruction, even at birth (e.g., Clark et al, 2014;Guttorm et al, 2001;Guttorm et al, 2003;Raschle, Zuk & Gaab, 2012;van Zuijen et al, 2012). It has been claimed, however, that the dissimilarities seen between the brain responses of dyslexics and controls at school age and as adults could in fact be caused by differences in reading experiences instead of being inherited.…”
Section: The Effect Of Familial Risk On Dyslexiamentioning
confidence: 99%
“…Furthermore, the combination of the right prefrontal activation in a rhyming task and the white matter organization in the left superior longitudinal fasciculus informed about the long-term reading gains of children with developmental dyslexia (Hoeft et al, 2011). Lately, it has been shown that structural as well as functional (Raschle, Zuk, & Gaab, 2012) differences related to dyslexia are already detectable in preschool children, before they learn to read (Raschle, Chang, & Gaab, 2010). In children with a high familial risk of developing reading problems, a reduced amount of grey matter was found in the bilateral parietotemporal and left occipito-temporal regions (Raschle et al, 2010).…”
Section: S Brem Et Al the Visual N1 As A Predictor For Reading Outcmentioning
confidence: 99%